Cultivating Microalgae Botryococcus braunii in Tofu Whey Medium - Marcelinus Christwardana; H. Hadiyanto (BIORE Scientia Publisher, 2022)
Tofu waste water is still being a significant issue in Indonesia owing to its level of BOD (Biological Oxygen Demand) and COD (Chemical Oxygen Demand) (Chemical Oxygen Demand). However, this waste also includes significant ammonia (230 mg/L) which is needed for microalgae development. Microalgae are photosynthetic microorganism which need nitrogen supply for their development. Among others, microalgae Botryococcus braunii is the one with large oil amount within their cells (25 – 75 %). This study was meant to examine the usage of tofu whey for culture medium for algae development. The experiment was done by adjustment of whey volume (5-20 %) in fresh medium and algal biomass was continually measured. The findings revealed that Botryococcus braunii obtained optimum growth in 10 % volume with biomass generated at 2.4 g/L and 0,8716 g/L of lipid production. At this circumstance, COD might be lowered up to 83.33 %.